Practical neurophysiological analysis of readability as a usability dimension - Oliveira, I. (2017)
This paper discusses opportunities and feasibility of integrating neurophysiologic analysis methods, based on electroencephalography (EEG), in the current landscape of usability evaluation methods. The rapid evolution and growing availability of low-cost, easier to use devices and the accumulated knowledge in feature extraction and processing algorithms allow us to foresee the practicality of this integration. The work presented in this paper is focused on reading and readability, identified as a key element of usability heuristics, and observable in the neurophysiologic signals' space. The experiments are primarily designed to address the discrimination of the reading activity (silent, attentive and continuous) and the verification of decreasing readability, associated with the user's mental workload analysis. The results obtained in the series of experiments demonstrate the validity of the approach for each individual user, and raise the problem of inter-subject variability and the need for designing appropriate calibration procedures for different users.